Perancangan Kendali Transformator Multiinput Berbasis Arduino Pada Pembangkit PV 9 X 10 WP - Tommy Adrian Sinaga; Antonius Rajagukguk; Fri Murdiya (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
There were several issues that could interfere with large-scale PV performance. The shading effect on the PV array caused reduced absorption of solar radiation in the modules in the PV array. The reduced absorption of solar radiation results in a decreased in the voltage on the PV string and disrupted the performance of the PV array system. This study designed a miniature PV farm with a small capacity consisting of 9 PV modules of 10 watt-peaks arranged to form 3 strings and each string consisting of 3 PV modules. This research used a bypass diode circuit and a blocking diode. In this study, the PV output voltage would be classified based on the voltage reading at each PV sting. The voltage at the time of the 3rd string was not exposed to small shading of 53 volts, greater than 36 volts, when 1 string was shade, the resulting voltage was smaller than 35 volts and a larger of 18 volts, while when 2 strings were shade, the resulting voltage is less than 17 volts. The output voltage of the PV is in the form of a DC power source, therefore an inverter was need that could convert it into an AC power source. Due to the small output voltage of the PV to be able to supply the feed load, a step up transformer was need. In this research, the transformer was design to be able to accept various input from PV. So a transformer with a variable input was design with a control on the primary winding to adjust the winding that would be active according to the sensor reading at the transformer input. And in the secondary winding of the transformer, a sensor was also installed to take a reading of the transformer output voltage to keep the voltage ± 220 volts.Keywords: Shading, Voltage, Photovoltaic, PV Farm, Inverter, Transformer